Development of real-time loopmediated isothermal amplification and PCR assays for detection of human papillomavirus 16 in oral squamous cell carcinoma - Hamzan, Nurul Izzati (2020)
Human papillomavirus genotype 16 (HPV-16) involvement in the development of oral squamous cell carcinoma (OSCC) has been well-documented. Its detection is crucial to classify OSCC into positive and negative cases; as this affects prognosis. The conventional method of detection for high-risk HPV relies upon p16 immunohistochemistry (IHC) as a surrogate marker which has drawbacks on its lengthiness, low specificity level (46 to 78%), broad range of staining intensity cut-off value (range 5 to 75%), requirement of expertise and costly. Thus, in an effort to improve the diagnostic test for HPV-related oral cancer, we have developed a realtime LAMP (qLAMP) assay for rapid, sensitive, specific and quantitative detection of HPV-16 in OSCC. The first phase was focused on the development of qLAMP and PCR assays, while in the second phase the developed assays were evaluated using OSCC clinical samples (tissue, n=63; saliva, n=13; and blood, n=59) and healthy (saliva, n=50). The hematoxylin and eosin (H&E) and p16 IHC staining using formalin-fixed paraffin embedded (FFPE) tissues was done to evaluate the tumour histological grading and determine high-risk HPV positivity, respectively. The Kappa value was determined between two raters for p16 staining. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy of qLAMP were evaluated, in comparison with PCR and p16 IHC. It was found that the developed qLAMP assay successfully amplified HPV-16, and no cross-reaction with other HPV strains, respiratory viruses and oral bacterial. The positive amplification starts as early as 21:18 minute and the whole process can be completed within one hour. The LOD for qLAMP and PCR assays were 4.68 X 101 and 4.68 X 103 copies per microliters, respectively. The developed qLAMP assay detected HPV-16 positivity in three tissue (4.7%) and saliva (23%) samples from OSCC patients, while the PCR assay detected two (3.17%) HPV-16 positives in tissue and one (7.69%) in saliva samples, with the HPV-16 viral load ranging from 4.68 X 101 to 4.68 X 104. The sensitivity, specificity, PPV, NPV and accuracy of qLAMP assay towards p16 IHC were 100%. The sensitivity, specificity, PPV, NPV and accuracy of in-house PCR assay were 67%%, 100%, 100%, 98% and 98%, respectively. p16 IHC staining showed three positivity of tissues with the H score ranged from 40 to 225% and welldifferentiated grade. Very good agreement (қ = 1.0) was found between two raters for evaluation of p16 IHC staining. In conclusion, the developed qLAMP was highly sensitive and specific, and rapid for the detection of HPV-16 in OSCC. This study is novel as it is the first report describing the use of both tissue and saliva as the sample matrix for detection of HPV-16 in OSCC and the detection platform using real-time to quantify the viral load of the infection in comparison to the current available HPV-16 detection kit.